Shear Bond Strengths and Morphological Evaluation of Filled and Unfilled Adhesive Interfaces to Enamel and Dentine - Vajihesadat Mortazavi; Mohammadhosein Fathi; Ebrahim Ataei; Niloufar Khodaeian; Navid Askari (International Journal of Dentistry)
In this laboratory study shear bond strengths of three filled and one unfilled adhesive systems to enamel and dentine were compared. Forty-eight extracted intact noncarious human mandibular molars were randomly assigned to two groups of 24 one for bonding to enamel and the other for bonding to dentine. Buccal and lingual surfaces of each tooth were randomly assigned for application of each one of filled (Prime & Bond NT (PBNT), Optibond Solo Plus (OBSP), and Clearfil SE Bond (CSEB)) and unfilled (Single Bond (SB)) adhesive systems (n=12). A universal resin composite was placed into the translucent plastic cylinders (3 mm in diameter and 2 mm in length) and seated against the enamel and dentine surfaces and polymerized for 40 seconds. Shear bond strength was determined using a universal testing machine, and the results were statistically analyzed using two-way ANOVA, one-way ANOVA, t-test, and Tukey HSD post hoc test with a 5% level of significance.There were no statistically significant differences in bond strength between the adhesive systems in enamel, but CSEB and SB exhibited significantly higher and lower bond strength to dentine, respectively, than the other tested adhesive systems while there were no statistically significant differences between PBNT and OBSP.